Dried small fish provide nutrient densities important for the first 1000 days - Byrd, K.A.; Pincus, L.; Pasqualino, M.M.; Muzofa, F.; Cole, Steven M. (Wiley, 2021)
Inadequate nutrient intakes are prevalent among many populations in sub-Saharan Africa and increasing fish consumption among pregnant/lactating women and children is one strategy to improve diets and address nutrient deficiencies. We report the nutrient content of two fish-based recipes—fish powder and fish chutney—that contain dried small fish available in local markets in Zambia. The contribution of a serving of each recipe to the recommended daily intakes of iron, zinc, calcium and docosahexaenoic acid (DHA) for pregnant/lactating women and children 6–24 months was calculated because these nutrients are commonly deficient in African diets. We found that one 10-g serving of fish powder provides 20% or more of the daily calcium recommendation and 37% or more of the daily DHA recommendation for both pregnant/lactating women and children. A 30-g serving of fish chutney provides over 40% of the daily calcium recommendation for pregnant women and over 50% for lactating women. Additionally, we investigated the nutrient density (nutrients per kilocalorie) of the fish powder and compared it with the nutrient density of a small-quantity lipid-based nutrient supplement plus (SQ-LNS-plus). SQ-LNS-plus is designed to enhance children's diets by providing micronutrients and DHA. Fish powder is similar to SQ-LNS-plus in iron and zinc density and even higher in calcium and DHA density. Consuming dried small fish as part of a daily meal can be a viable strategy for combatting nutrient deficiencies in the first 1000 days.